Mechanosensitive Piezo1 in Periodontal Ligament Cells Promotes Alveolar Bone Remodeling During Orthodontic Tooth Movement - Jiang, Yukun; Guan, Yuzhe; Lan, Yuanchen; Chen, Shuo; Li, Tiancheng; Zou, Shujuan; Hu, Zhiai; Ye, Qingsong (Frontiers in Physiology, 2021)
Orthodontic tooth movement (OTM) is a process depending on the remodeling of periodontal tissues surrounding the roots. Orthodontic forces trigger the conversion of mechanical stimuli into intercellular chemical signals within periodontal ligament (PDL) cells, activating alveolar bone remodeling and thereby initiating OTM. Recently, the mechanosensitive ion channel Piezo1 has been found to play pivotal roles in different types of human cells by transforming external physical stimuli into intercellular chemical signals. However, the function of Piezo1 during the mechanotransduction process of PDL cells has rarely been reported. Herein, we established a rat OTM model to study the potential role of Piezo1 during the mechanotransduction process of PDL cells and investigate its effects on the tension side of alveolar bone remodeling. A total of sixty male Sprague-Dawley rats were randomly assigned into three groups: the orthodontic tooth movement + inhibitor group (OTM + INH), the orthodontic tooth movement group (OTM), and the control group (CON). Nickel-titanium orthodontic springs were applied to trigger tooth movement. Mice were sacrificed on days 0, 3, 7, 14 after orthodontic movement for radiographic, histological, immunohistochemical, and molecular biological analyses. Our results revealed that the Piezo1 channel was activated by orthodontic force and mainly expressed in the PDL cells during the whole tooth movement period. The activation of Piezo1 channel was essential for maintaining the rate of orthodontic tooth movement and facilitation of new alveolar bone formation on the tension side. Reduced osteogenesis-associated transcription factors Runt-related transcription factor 2 (RUNX2) and Osterix (OSX), and NF-κB ligand (RANKL)/osteoprotegerin (OPG) ratio were examined when the function of Piezo1 was inhibited. In summary, Piezo1 plays a critical role in mediating both osteogenesis and osteoclastic activities on the tension side during OTM.